Penggunaan Heat Pipe Persegi dan Sirip Untuk Meningkatkan Performance Pada Flat Plate Solar Collector - Rabiatul Adawiyah; M. Khafidz Arifin (POROS TEKNIK, 2016)
Based on the review of references from journals, and review of the literature supportingthis research, state of art the underlying issue of solar collectors in particular types of flatplate solar collector how to improve performance such as efficiency the collector can beincreased maximum. In improving this performance history researchers perform a variety ofways, that is modification, add fixtures, test material used etc. From the results of researchrelated to the problem of the increase in performance use of hosepipes connected with theuse of heat pipe absorber all round. This raises a hypothesis in which the surface directlyexposed to hot sun or in contact with the absorber a little part of the arch so that the surfacearea too small conduction, if used pipes square shape is expected to occur heat absorptionis better because of surface conduction wider and coupled with a fin heat sink.Based on the above, the underlying issue is the increase in performance generated inthe form of heating efficiency, is to examine how they affect the use of heat pipe square andadded a fin on the top to the increased performance of the solar collector.The results of this study found that the performance of solar collector that uses squarepipe equipped with fins better than solar collector with a round pipe